Little value creation, articulation and propagating forces: A hypothesis for the Mexican manufacturing sector - Roca T, Santiago (2015)
This paper evaluates the impact of Mexican trade and productive integration processes during the last 20 years. It finds evidence that growing per capita income in Mexico is directly related to its “trade opening”, but is inversely related to the growth of its manufacturing export industry. Specifically, for each point of growth in “trade opening” (as a proportion of GDP) per capita income grew by 0.22%; while each point of increase in the share of industrial exports reduced income per person by 0.09%. To explain this apparent contradiction between the positive effect of “trade opening” and the negative impact of productive manufacturing specialization, we examined the characteristics of Mexico’s industry. Results show that although Mexico’s export-led industrialization successfully adapted to the world market and transformed its productive, business, organizational and technological structure, it did not translate into adequate macroeconomic benefits due to the absence of strong value dissemination forces over the rest of the economy. In this sense, poor internal linkages in the maquila industry, its high propensity to import, and its limited value added generation, among other elements, led the Mexican industry to operate as an export enclave. In those circumstances, manufacturing does not generates positive externalities nor articulations, nor strong disseminations that increase and multiplies value in other sectors of industry, thus limiting expansion effects and restraining or even reducing–under some specific circumstances–per capita income growth. Doi: http://dx.doi.org/10.1016/j.jefas.2015.08.003